Uterine didelphys with obstructed hemivagina and ipsilateral renal anomaly - OHVIRA syndrome: a rare congenital anomaly - Patil, Bhimarao; Nagaraju, Rashmi Mysore (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
OHVIRA or Herlyn-Werner-Wunderlich syndrome is a rare congenital anomaly characterized by uterine anomaly with obstructed hemivagina and ipsilateral renal anomaly. We present a case of 16 year female who presented with cyclical lower abdominal pain. Ultrasonography and computed tomography in this patient revealed classic triad of findings. Our case is significant as the diagnosis was made at an earlier stage of the disease before development of gross obstruction and hematometrocolpos.